Response of Drought Tolerant and Conventional Corn to Limited Irrigation - I. Kisekka; F. Lamm; J. D. Holman (Kansas Agricultural Experiment Station Research Reports, 2015)
With declining water levels in the Ogallala aquifer, many wells cannot supply peak irrigation water needs for corn. Emerging drought-tolerant (DT) corn hybrids could help farmers maintain yield with limited capacity wells. A knowledge gap exists comparing transgenic DT and conventional corn hybrids in yield response to water level. The purpose of this study was to compare yield, yield components, water productivity, and irrigation water use efficiency response of DT corn with cspB (DKC 6267 DGVT- 2PRO) transgene trait and conventional corn hybrid (DKC 62-98 VT2PRO) with similar maturity to full and limited irrigation. Preliminary results from the 2014 growing season indicate the effect of irrigation level on corn yield was significant (P-value<0.001). The effect of the cspB transgene trait in the DT hybrid did not affect yield (P-value=0.32), and there was no effect of the interaction between irrigation level and corn hybrid on yield (P-value=0.82). The effect of irrigation and hybrid on 100 kernel weight was significant, with P-value<0.001 and P-value<0.001 respectively. The 100 kernel weight is a measure of kernel size, and was higher for the conventional hybrid compared to the DT hybrid.
Keywords: irrigation; corn; crop water; water supply; drought tolerant corn; DT hybrid; Ogallala Aquifer; yield response; water use efficiency